2018
DOI: 10.3389/fchem.2018.00478
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Behavior of Chromium and Yttrium Molybdate (Cr2Mo3O12, Y2Mo3O12)

Abstract: The high pressure behavior of negative thermal expansion materials continues to be of interest, as their potential use in controlled thermal expansion composites can be affected by irreversible pressure-induced phase transitions. To date, it is not possible to predict the high pressure behavior of these compounds, necessitating measurements on each composition. In this work, high pressure synchrotron powder X-ray diffraction studies of Cr2Mo3O12 and Y2Mo3O12 were conducted in a diamond anvil cell. Chromium mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…A direct reduction of the bulk modulus by entropic elasticity (i.e., an increase in entropy upon compressive strain) has been found in floppy networks, including ScF 3 (Tkachenko and Zaliznyak, 2021), indicating an underlying mechanism that reduces the bulk modulus in flexible frameworks. This relationship is not absolute (e.g., α-ZrW 2 O 8 is stiffer than the thermomiotic A 2 M 3 O 12 oxides and has a more negative CTE (Drymiotis et al, 2004;Varga et al, 2006;Young et al, 2018)), because the Grüneisen parameters of thermomiotic materials vary considerably, and because of the effects of anisotropy, which require further discussion.…”
Section: Thermomechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct reduction of the bulk modulus by entropic elasticity (i.e., an increase in entropy upon compressive strain) has been found in floppy networks, including ScF 3 (Tkachenko and Zaliznyak, 2021), indicating an underlying mechanism that reduces the bulk modulus in flexible frameworks. This relationship is not absolute (e.g., α-ZrW 2 O 8 is stiffer than the thermomiotic A 2 M 3 O 12 oxides and has a more negative CTE (Drymiotis et al, 2004;Varga et al, 2006;Young et al, 2018)), because the Grüneisen parameters of thermomiotic materials vary considerably, and because of the effects of anisotropy, which require further discussion.…”
Section: Thermomechanical Propertiesmentioning
confidence: 99%
“…Note that A 2 M 3 O 12 and related filler materials are frequently prone to pressure-induced transformation from the desired orthorhombic phase to the monoclinic phase at pressures <250 MPa (Varga et al, 2005), with some exceptions such as Zr 2 WP 2 O 12 which is still orthorhombic at pressures as high as 300 MPa . Such transformation must be considered in selecting the compaction pressure value for the green CMCs prior sintering (Young et al, 2018). The compaction pressures reported for these CMCs (see Table 1), ranged between 50 and 245 MPa, and did not induce the unwanted phase transition.…”
Section: Ceramic Matrix Composites (Cmcs)mentioning
confidence: 99%
“…In order to understand the NTE mechanisms in Y 2 Mo 3 O 12 , several studies have been performed: the relation between AO 6 polyhedral distortion and NTE in orthorhombic Y 2 Mo 3 O 12 [16], and the effect of water species on the phonon modes [11,17]. There are many studies to improve the NTE properties in Y 2 Mo 3 O 12 [18,19], and to characterize various properties of Y 2 Mo 3 O 12 [20][21][22]. These studies have shown that the hygroscopicity is related to the sizes of cations A, and the reduction of hygroscopicity is achieved by substituting trivalent cations to Y 3+ sites [10,23].…”
Section: Introductionmentioning
confidence: 99%